Lean Hospital Approach to Identify Critical Waste in the Outpatient Pharmacy Instalation of RSI PKU Muhammadiyah Pekajangan - Lusi Rahmani Putri; Susanto Susanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
This Research Purpose to identify critical waste, root cause of critical waste, up to giving recommended improvement to minimize critical waste in the outpatient pharmacy. This research uses qualitative approach with case study design. The health service process is visualized with value stream mapping, the amount of critical waste is obtained by distributing questionnaires, while the root cause of critical waste is acquired by 5 why method of interview. The recommended improvementis accomplished by discussion between team and expert panel. Based on the value stream mapping, it has obtained 16,67% of ratio value added to waste for non concoction prescription and 14.52% of ratio value added to waste for concoction prescription. Based on waste questionnaire distribution, motion got the highest rank as the most often exist waste with 19% percentage. The root causes of this motion waste is nonexistence of a routine schedule on the work space organization, which affecting the effectiveness of pharmacy staff to complete their task. The recommended improvement to minimize this waste motion is to conduct 5S method.